Internalisasi Nilai-Nilai Moderasi Beragama Melalui Kearifan Lokal Bugis Makassar: Studi Multi-Situs di Sekolah Menengah Atas Islam - Ardiyansyah Ardiyansyah; M. Afif Zamroni; Rahmat Rahmat; Asep Saepuddin Chalim (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study examines the process of value internalization in fostering students’ attitudes of religious moderation. The research aims to identify and articulate the concept of value internalization in relation to strengthening students’ moderation attitudes from the perspective of Bugis–Makassar local wisdom. The study employs a qualitative multisite approach in two madrasahs in Bulukumba Regency, referring to Robert K. Yin’s model. Data were collected through observation, interviews, and documentation. The findings of this study provide an important contribution to elaborating the theory of value internalization proposed by Emile Durkheim and Muhaimin within the context of value cultivation, by exploring how elements of local wisdom are internalized by students as part of efforts to strengthen attitudes of religious moderation. The formal finding of this research is the formulation of the PINTAR value-internalization concept, which consists of Environmental Conditioning, Habituation, Experience, Transinternalization, Appreciation through Reward and Punishment, and Role Modeling.